ANALISIS HUKUM PUTUSAN PENGADILAN DALAM PENETAPAN PERWALIAN ANAK DI BAWAH UMUR DI PENGADILAN NEGERI - Nisa , Azzahra Latifatun (Muadalah : Jurnal Hukum, 2024)
Guardianship Application Case Number 70/Pdt.G/2023/PN Son submitted to the District Court, in its ruling granted the applicant's request, namely by establishing the Applicant as guardian for his biological child. Meanwhile, Article 47 of Law Number 16 of 2019 concerning Marriage explains that, “Children who have not reached the age of 18 (eighteen) years or have never entered into marriage are under the authority of their parents as long as they are not deprived of their authority”. The granting of guardianship rights to a person is given through a trial in which the Court has the authority to grant it. The right of guardianship is exercised and given to someone to represent the child in carrying out legal acts and the interests of the child and includes the right of admission, property, and management of goods. Guardianship of children is regulated in the Civil Code, Law, and also KHI. The guardian is appointed by the Court to carry out his obligations properly in caring for minors and is responsible for the property of children under guardianship, as well as losses arising from his mistakes or negligence. Guardianship is granted if the parents of the child have passed away, so that the child gets the inheritance from his parents. The Panel of Judges considered the decision of the petition with the aim of the interests of the minor. With the legal basis used by the Panel of Judges in deciding this case including Marriage Law Article 50 No.1/1974, Article 51 paragraph (2) of Law No.1/1974, from this research the granting of applications for guardianship of minors so that children who have been left by their parents can remain protected, both in terms of growth and development and protection of property after the death of their parents.